Moderating Effect Of Organizational Factors Between Competitive Intelligence Practices And Performance Of Firms Listed On The Nairobi Securities Exchange, Kenya - Waithaka, Paul (European Scientific Journal, ESJ, 2016)
Performance is critical for every listed firm, as it enhances shareholder’s value and capability to generate earnings from invested capital. Some of the firms listed on the Nairobi Securities Exchange (NSE) have been performing poorly as indicated by the rising number of firms issuing profit warnings. The competitive business environment is continuously working to drive down the rate of return on invested capital. To counter these competitive forces, firms have resorted to gathering information at their disposal and converting it into competitive intelligence through analysis and human judgment. Competitive intelligence can be viewed both as a process and a product. As a process, it is the set of legal and ethical methods for collecting, developing, analyzing and disseminating actionable information pertaining to competitors, suppliers, customers, the organization itself and business environment that can affect a company’s plans, decisions and operations. Competitive intelligence as a product is information about the present and future behavior of competitors, suppliers, customers, technologies, government, market and the general business environment. This study sought to determine the moderating effect of organizational factors between competitive intelligence practices and performance of firms listed on the NSE. Firm performance was evaluated using both financial and non-financial measures. The findings indicate that organizational factors specifically organizational culture, organizational structure and managerial attitudes toward competitive intelligence were found to moderate in the relationship between the competitive intelligence practices and performance of firms listed on the NSE, Kenya.